Post-Disaster Needs Assessment : Lessons from a Decade of Experience - Jeggle, Terry (European Commission, GFDRR, UNDP, and the World Bank, 2018)
As natural disaster events continue to occur with increasing frequency at greater material and human costs globally, there is an imperative need for countries to recover from these disasters’ damaging effects with increased national resilience. The extent to which that information can be obtained in a way that balances timeliness with comprehensiveness, and is accurate and justifiable, will accelerate recovery initiatives. Post-disaster needs assessments (PDNAs) is an internationally accepted methodology for determining the physical damages, economic losses, and costs of meeting recovery needs after a natural disaster through a government-led process. This PDNA review is the first instance of the participating institutions assessing the demonstrated effectiveness of PDNAs, as the practice has evolved over the fifty five post-disaster assessments conducted since 2008. The United Nations Development Programme (UNDP) and the Global Facility for Disaster Reduction and Recovery (GFDRR) of the World Bank Group have undertaken the review with support from the European Union between March and June 2017. The review focuses on ten areas of inquiry and draws on a sample of fourteen PDNAs. The countries that were included in the PDNA review were distributed across global regions and demonstrated both shared and contrasting geophysical, socioeconomic, political, and cultural characteristics. This review includes discussions with tripartite institutions and selected countries that have undertaken PDNAs.